철도시스템 소프트웨어 변경영향 분석을 위한 자동화 도구 개발 - 조현정(Hyun-Jeong Jo); 황종규(Jong-Gyu Hwang); 김용규(Yong-Kyu Kim) (전기학회 논문지 P권, 58(2), 2009)
Recent advances in computer technology have brought more dependence on software to railway systems. Hence, the safety assurance of the vital software running on the railway system is very critical task and yet, not many works have been done. While much efforts have been reported to improve electronic hardware's safety, not so much systematic approaches to evaluate software's safety. In this paper, we suggested an automated analysis tool for S/W change impact in railway system, and presented its result of implementation. The analysis items in the implemented tool had referred to the international standards in relation to the software for railway system, such as IEC 61508 and IEC 62279. In these international standards, 'change impact analysis' for railway system S/W has to be required mandatorily. The proposed tool can be utilized at the assessment stage and also the software development stage.